Developing Cost-Effective and High-Speed 40 Gbps FSO Systems Incorporating Wavelength and Spatial Diversity Techniques - Modalavalasa, Satish Kumar; Miglani, Rajan; Chaudhary, Sushank; Tubbal, Faisel; Raad, Raad (Frontiers in Physics, 2021)
Free space optical (FSO) communication systems are being anticipated to offer promising alternatives to existing radio networks in delivering high-speed data access to end-users. Ease of installation, robust features, and cost-effective operation have been the hallmarks of the FSO system and these features will play an obvious role in deciding the ways in which futuristic smart communication models will operate. Despite these arrays of features, FSO links suffer severe performance degradation due to channel-induced impairments caused by atmospheric effects such as rain, haze, and fog. In this work, we have investigated and compared the performance of 40 Gbps FSO link for different channel conditions ranging from clear weather to severe attenuation, by incorporating spatial and wavelength diversity as performance booster techniques. The use of Erbium-doped fiber amplifier (EDFA) with FSO links has also been proposed here. Using performance metrics like bit error rate (BER) and eye patterns, it has been found that use of EDFA not only helps to compensate for the link losses but also aids in realizing an all-optical processing based last-mile access system.